Frekuensi konsumsi makanan instan dan stunting pada anak usia 6-23 bulan - Manalu, Keysa Novita; Nai, Hildagardis Meliyani Erista; Pujiastuti, Veronica Ima (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2024)
Frequency of instant food consumption and stunting in children aged 6-23 monthsBackground: Stunting is related to feeding patterns: breastfeeding and complementary foods, especially in the first two years of life. Many commercial complementary food products, such as instant powder and biscuits, still do not meet iron and zinc content requirements.Objective: This study aims to determine the relationship between the frequency of instant food consumption and the incidence of stunting in children aged 6-23 months in Sleman Regency. Methods: This study is an analytic observational study with a cross-sectional design. The research sample was children aged 6-23 months in the working areas of the Minggir Public Health Center, Pakem Public Health Center, and Ngemplak 1 Public Health Center. The sample size for this study was 265 people, consisting of 125 boys and 140 girls. The sampling technique used simple random sampling. Data collected included the characteristics of the research subjects and respondents, frequency of instant food consumption, incidence of stunting, and history of infectious disease. Data analysis used the Chi-Square test. Results: Most children were not stunted (70.6%) and consumed instant food often (58.9%). There was no relationship between the frequency of instant food consumption and the incidence of stunting (p>0.05). There was no significant relationship between gender, age, history of diarrhea, history of pneumonia, mother's education level, mother's employment status, family income, number of family members, and frequency of instant food consumption with the incidence of stunting (p>0.05). A significant relationship exists between the history of acute respiratory infection and the father's education level and stunting incidence (p<0.05). Conclusions: There is no significant relationship between the frequency of instant food consumption and the incidence of stunting in children aged 6-23 months. Future research can examine the frequency of giving instant food by considering instant food portions.